An Evaluation on the Contribution of Turkish Culture to Turkish Teaching [North Macedonia] in the Works of Yeni Balkan Publishing House between 2010-2022 - Sarıtunç, Berrin
Language is a systematic structure created by rules. Being able to understand and interpret what you listen and read is related to the correct use of language. This happens when people have language awareness. Language awareness is also the strongest bond that holds societies together. The press is very important in ensuring this bond. In this context, in the Balkans, which is the subject of our study, languages other than Turkish are also used and take place in schools and in the press. Although languages such as Albanian, Macedonian and Serbian, which are used outside of Turkish, are of course accepted as a wealth, attention should be paid to the use of Turkish for the realization of cultural transfer, social unity, belonging and the awareness of being a nation, and it should have a wide area of use in the press and broadcasting life. As it is known, the media is one of the greatest forces in directing societies. Since the Balkans is a region where many different nations live together, ethnic conflicts have also been experienced, and the media has been exposed to the shaping of these conflicts. Media life in Macedonia, which was an important cultural center during the Ottoman Empire, maintained the same mobility after the disintegration of Yugoslavia. In this context, it is seen that the publications in the region are one of the key stones in the Turkish ideal. New Balkan Publishing's organization of studies that encourage the use and teaching of Turkish, the motifs of Turkish culture and people (manies, lullabies, Nasrettin Hoca, Keloğlan, Mevlana, Yunus Emre, Hacı Bektaşi Veli, Süleyman Çelebi, Ömer Seyfettin, Şemsettin Sami, Mehmet Akif) Ersoy, Yahya Kemal Beyatlı, Aliya İzzetbegovic) seems to have undertaken an important mission in the Balkans with his contribution and support to the publication of the works. For this reason, the aim of our study is to examine more than 100 works of the publishing house between the years 2010-2022 in terms of the transfer of Turkish and Turkish culture. In our ...